A Generalized Packing Model for Bulk Crystalline Regioregular Poly(3‐alkylthiophenes) with Extended Side Chains. Issue 3 (20th July 2017) - Bohle, Anne; Dudenko, Dmytro; Koenen, Nils; Sebastiani, Daniel; Allard, Sybille; Scherf, Ullrich; Spiess, Hans Wolfgang; Hansen, Michael Ryan
Abstract: Poly(3‐alkylthiophenes) are one of the most frequently used conjugated polymer classes in organic photovoltaics. Here, a generalized packing model for the polythiophene main chains in the crystalline form I of high molecular weight regioregular poly(3‐alkylthiophenes) with extended side chains (pentyl through octyl) is reported. The model is based on structural constraints from solid‐state NMR: short internuclear distances of less than 4.0 Å of neighboring thiophene protons parallel to the stacking direction and the isotropic chemical shift for the thiophene protons is high‐field shifted by 0.9 ± 0.1 ppm. Nucleus‐independent chemical shift calculations show that only the most recent structure for P3HT (space group P2 1 / c ) is compatible with these structural constraints. On this basis, a generalized packing model is developed, showing that slipping parallel to the stacked polymer chains of up to 1.5 Å is allowed, while out‐of‐plane tilts perpendicular to the stacked chains are only tolerated up to 20°. Abstract : The crystalline form I of regioregular poly(3‐alkylthiophenes) with extended side chains is shown to crystallize in the space group P21 /c from a combination of solid‐state NMR experiments and condensed‐phase nucleus‐independent chemical shift calculations.